Роман «Агнець» Крістофера Мура як літературне Євангеліє - Березіна, Д. (Літературознавчі обрії. Праці молодих учених, 2010)
The typical features of the literary gospel as a genre are stated. The peculiarities of the transformation which the Gospel myth undergoes in the novel of Christopher Moore are analyzed. Special attention is focused on the elements of the mass culture the author uses to modernize the original myth.